The Chilling Effect of International Investment Law and Indonesia’s Preventive Steps to Overcome It - Simbolon, Putu George Matthew; Oktavani Yenny (Jurnal Kajian Pembaruan Hukum, 2025)
This research is necessary due to the chilling effect brought about by the IIL and the provision under Article 32 of the Indonesian Capital Investment Law, which potentially brings adverse effects to the Government of Indonesia. Such adverse effects can manifest as substantial compensation claims and policy adjustments contrary to national interests. Unlike previous research concerning Indonesia prior to the IIL regime, the distinctive feature of this study is the implementation of the exhaustion of local remedies doctrine based on IIL doctrines, past ICSID cases, and dispute settlement procedures under BITs. This research comprises four discussions outlined below. The first discussion outlines prior research concerning Indonesia before the IIL regime, along with the novelty discussion. Meanwhile, the second discussion explains the adverse effects of ISDS and SSID on Indonesia's sovereignty and its diplomatic relations with other ICSID Convention members. The third discussion emphasises that Indonesia should not perceive the IIL as an isolated regime, allowing it to utilise this legal framework to prevent disputes through international arbitration and adopt objective investment measures. Lastly, the fourth discussion describes how Indonesian local courts should be employed to resolve foreign investment disputes. The expected contribution of this research is to enrich the literature concerning IIL from an Indonesian law perspective. Furthermore, this research is crucial to serve as guidance for Indonesian lawmakers when amending Article 32 of the Capital Investment Law.